Rational quiver representations: tame and wild - Januszewski, Fabian (arXiv:2510.00924)
We study representation finite $K$-rational quivers over fields of characteristic $0$ and their indecomposable representations, exploiting that all Brauer obstructions for descent of representations are trivial in this case. Contrasting the tame case, we give an example of a simple quiver of wild representation type, where we realize every possible Brauer obstruction of a given Galois extension $L/K$ in the category of quiver representations over $L$.

"One-sided, prejudiced view of Germans": Das Ressentiment als literarischer Ausdruck jüdischer Antiversöhnlichkeit bei Olga Grjasnowa und Dana Vowinckel - Spener, Anna Maria (Rückkehr des Ressentiments? Stereotype in Medien, Kulturphilosophie und Literatur (Sonderheft der Zeitschrift für deutsche Philologie))

Algorithmische Kulturen des Pflanzensammelns? Das Beispiel der Computerisierung des Botanischen Gartens und Botanischen Museums Berlin - Alpsancar, Suzana (Algorithmische Wissenskulturen. Der Einfluss des Computers auf die Wissenschaftsentwicklung)

Healthy Distrust in AI systems - Paaßen, Benjamin; Alpsancar, Suzana; Matzner, Tobias; Scharlau, Ingrid (arXiv)
nder the slogan of trustworthy AI, much of contemporary AI research is focused on designing AI systems and usage practices that inspire human trust and, thus, enhance adoption of AI systems. However, a person affected by an AI system may not be convinced by AI system design alone---neither should they, if the AI system is embedded in a social context that gives good reason to believe that it is used in tension with a person’s interest. In such cases, distrust in the system may be justified and necessary to build meaningful trust in the first place. We propose the term healthy distrust to describe such a justified, careful stance towards certain AI usage practices. We investigate prior notions of trust and distrust in computer science, sociology, history, psychology, and philosophy, outline a remaining gap that healthy distrust might fill and conceptualize healthy distrust as a crucial part for AI usage that respects human autonomy.

From Explaining to Diagnosing: A Justice-Oriented Framework of Explainable AI for Bias Detection - Fahimi, Miriam; State, Laura; Kasirzadeh, Atoosa (Proceedings of the AAAI/ACM Conference on AI, Ethics, and Society)
Explainable AI (XAI) methods can support the identification of biases in automated decision-making (ADM) systems. However, existing research does not sufficiently address whether these biases originate from the ADM system or mirror underlying societal inequalities. This distinction is important because it has major implications for how to act upon an explanation: while the societal bias produced by the ADM system can be algorithmically fixed, societal inequalities demand societal actions. To address this gap, we propose the RR-XAI-framework (recognition-redistribution through XAI) that builds on a distinction between socio-technical and societal bias and Nancy Fraser's justice theory of recognition and redistribution. In our framework, explanations can play two distinct roles: as a socio-technical diagnosis when they reveal biases produced by the ADM system itself, or as a societal diagnosis when they expose biases that reflect broader societal inequalities. We then outline the operationalization of the framework and discuss its applicability for cases in algorithmic hiring and credit scoring. Based on our findings, we argue that the diagnostic functions of XAI are contingent on the provision of such explanations, the resources of the audiences, as well as the current limits of XAI techniques.

Standardising Equality in the Algorithmic Society? A Research Agenda - Xenidis, Raphaële; Fahimi, Miriam (Proceedings of Fourth European Workshop on Algorithmic Fairness)
In 2024, the EU adopted the AI Act, a new set of rules for trustworthy artificial intelligence. This legal instrument carves a large place for standardisation, a regulatory technique that consists in crafting so-called harmonised technical standards, to facilitate legal compliance by industry stakeholders. While EU technical standards have been used in the past for ensuring product safety, for the first time the AI Act relies on standardisation to facilitate compliance with fundamental rights, including the right to non-discrimination and equality. The attempt to translate inherently open-textured rights and ethical principles into operationalizable standards raises critical questions. In particular, how will standardisation practices under the new EU AI Act affect, transform, contest and stabilise notions of equality and non-discrimination in an increasingly algorithmic society? This paper proposes a research agenda to address this question and unpack the black box of AI standardisation.

L'islam dans la culture populaire: Reconfigurations et nouvelles visiblités
La France contemporaine révèle un large éventail d’expressions d’une conscience(franco-)musulmane plurielle et visible. Cet ouvrage se penche sur ces nouvelles visibilités de l’islam dans la culture populaire et accorde une importance particulière au protagonisme des femmes musulmanes ainsi qu’à la culture populaire dans l’espace numérique. Il démontre également que la quête d’une nouvelle visibilité est à la fois un moteur d’intégration et de productivité culturelle, mais aussi génératrice de conflits.

Hugo De Schepper: 'A latere principis u de su theniente general'. De regeringsraden naast landsheren en landvoogden in de Habsburgse Nederlanden: Leden, instellingen en algemene politiek, 1577/1580-1609, Leuven: Peeters 2023 - Huybrechts, Yves (Sehepunkte)

Szenarien digitaler Lehre: online, blended, hybrid und inverted - Neiske, Iris; Spannagel, Christian (Praxishandbuch Hochschullehre II)

Static Light Scattering for Lignin Particle Size Characterization - Makkonen, Janita; Ahvenainen, Patrik; Bertella, Stefania; Kellock, Miriam; Saha, Sanjib; Huber, Klaus; Farooq, Muhammad; Österberg, Monika; Penttilä, Paavo (Particle & Particle Systems Characterization)
Abstract Lignin, a widely available and renewable organic polymer, has several desirable properties and applications. However, as a by‐product of pulp and paper industry, it is mainly burned for energy. Limited understanding of the complex and heterogeneous structure and a shortage of tailored analysis methods hinder its utilization in higher value applications. This study describes and compares the use of two different static light scattering methods, laser diffraction and small‐angle light scattering (SALS), for studying lignin particle size in suspension. The results from laser diffraction showed that the selected particle concentration and absorption coefficient affect the measured sizes especially for particles <1 µm in diameter. For irregularly shaped particles with broad size distributions, sampling is the most important parameter affecting the results. SALS proved an efficient method for obtaining information on particle aggregation by providing primary particle sizes as well as aggregate sizes. Characterization of samples with spherical particles and narrow size distributions is straightforward with both laser diffraction and SALS, whereas the interpretation of results for more heterogeneous samples is less obvious. Static light scattering methods could make lignin particle size analysis more rapid and automated, thus enhancing lignin valorization, but should be applied carefully to avoid systematic errors.

Self-Assembly of Pseudo Isocyanine Chloride in the Presence of Attractive Polyethylene Glycol Crowders - Koch, Leon; Rajput, Satyendra; Richter, Antonio; König, Benedikt; Nayar, Divya; Ebbinghaus, Simon; Huber, Klaus (The Journal of Physical Chemistry B)

Analysis of the Growth Mechanism of Eumelanin Particles by Time-Resolved Static and Dynamic Light Scattering - Kollmann, Fabian; Büngeler, Anne; Splett, Miriam; Strube, Oliver I.; Huber, Klaus (Biomacromolecules)

Coil dimensions of macromolecules in the presence of crowding colloids: Impact of crowder size - Huber, Klaus; Martens, C.M.; Tuinier, R. (Journal of Colloid and Interface Science)

Philosophie und Ethik in der Lehrerinnen- und Lehrerbildung. Grundlagen und Perspektiven - Albus, Vanessa (Handbuch Lehrerinnen- und Lehrerbildung)

Rezension: La peinture murale en Alsace au coeur du Rhin supérieur du Moyen Âge à nos jours / Die Wandmalerei im Elsass im Herzen des Oberrheins vom Mittelalter bis heute - Heinrichs, Ulrike (The Burlington Magazine)

Monoton erreichbarer Delaunaygraph - Werner, Felix

Gott, heilger Schöpfer aller Stern (EG 3). Zum 500. Todestag von Thomas Müntzer (1489-1525) - Schroeter-Wittke, Harald (Praktische Theologie)

A 50 Gbps Reference-less NRZ Full-rate Bang-Bang CDR with Automatic Frequency Acquisition in 130 nm SiGe:C BiCMOS Technology - Iftekhar, Mohammed; Sadiye, Babak; Müller, Wolfgang; Scheytt, J. Christoph (IEEE Nordic Circuits and Systems Conference (NORCAS))

A 128 GS/s 2x Time-Interleaved Track and Hold Amplifier in 130nm SiGe BiCMOS - Weizel, Maxim; Malavalli Nagaraju, Harshan Gowda; Scheytt, J. Christoph (2025 IEEE BiCMOS and Compound Semiconductor Integrated Circuits and Technology Symposium (BCICTS))

Verilator and FireSim RTL Simulations on a HPC Cluster: A Comparative Case Study - Hannemann, Kai Arne; Bütün, Hüseyin Berke; Müller, Wolfgang; Scheytt, J. Christoph (MBMV 2025 - 28. Workshop Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen)